Death rides alone - Johnstone, William W.; Johnstone, J. A. (Waterville, Maine Wheeler Publishing, 2016)
Mountain Man Smoke Jensen's long-lost brother Luke Jensen is a deadshot scarred by war -- the perfect formula for a bounty hunter. And he's cunning, and fierce enough to bring down the deadliest outlaws of his day. Luke Jensen has earned this bounty, hunting down the violent man charged with murdering a preacher's daughter. The outlaw Judd Tyler confesses to many crimes, but not the girl's murder. And he tells Luke they won't reach the town of White Fork alive because a corrupt sheriff does the bidding of a cattle baron, and that man's son is the true killer. Sure enough, halfway to White Fork, Luke and his prisoner are battling for their lives, and when they finally reach town, they're greeted by a storm of bullets, betrayal, and blood. With a band of innocent travelers caught up in the melee, Luke is outgunned, surrounded, and sure of only this: his only job now is survival -- by the measured, efficient, righteous killing of as many men as he can.
104995
Keywords: Outlaws -- Fiction; Bounty hunters -- Fiction; Large type books; Western fiction; Fiction